Customer Satisfaction Analysis PT. Delta Nusa Abadi Through Servqual And AHP Method as Moderating Variables - Widhyanty, Windhy; Wulandari, Retno; Wibowo, Alif Junean (Universitas Budi Luhur, 2024)
This study aims to measure the level of service comfort and customer satisfaction with the services provided by event organizer service providers so that services are in accordance with consumer desires. For this reason, it is necessary to measure using analysis and the Servqual method and calculate each dimension with the Analytical Hierachy Process (AHP) method. Most service providers outside the city are very competitive, especially in Tangerang. Therefore, a service evaluation should be done to find out how comfortable and satisfied the customer is with the service provided by the service provider. This quantitative research uses numerical data and statistics to determine the influence of event organizers on customer satisfaction of PT Delta Nusa Abadi (DNA) Management. This research is quantitative with numerical and statistical data. Primary data, consisting of questionnaires, and secondary data, obtained through searching for relevant data, are used in the data collection process. The main purpose of data analysis techniques that use multiple linear regression analysis is to compete with other event hosting service providers. Customer satisfaction, service quality methods, and Analytical Hierarchy Process (AHP) are the key words chosen in the survey to measure the comfort level and customer satisfaction of event organizer service providers, that the unstandardized beta coefficient X3_M of 0.721 and the significance level of 0.032 which is smaller than 0.05. This positive regression coefficient means that service quality and analytical hierarcy process strengthen the relationship between price variables and customer satisfaction.